Analisis Multimodal pada Iklan Scarlett versi Song Joong Ki di Instagram - Putri, Yuli Aisyah (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
The complexity of meaning in advertising involves not only language elements that play a role in conveying meaning but also non-verbal language elements and other visual means. For that reason, a multimodal approach is needed to understand the complexity of meaning. The present article discussed a multimodal analysis of Scarlett's advertising images in collaboration with Song Joong Ki. The study used the analysis by Kress & Van Leeuwen's multimodal concept, which includes three dimensions of meta-functional analysis: representational, interpersonal, and compositional meta-functions. The current research design was qualitative descriptive, where the data were collected through documentation. The data source was a poster on the Instagram feed @scarlett_whitening depicting Song Joong Ki as a brand ambassador. The results showed that Scarlett advertisers aim to attract active consumers on social media through the portrayal of Song Joong Ki in the advertisement. Apart from that, the advertisement also represents a fantasy about a brightening and moisturizing body serum. Keywords: multimodality, social semiotics, advertising, Scarlett, Song Joong Ki